PENGARUH LATIHAN DRILL 11 TERHADAP KETERAMPILAN DRIBBLING KLUB SSB SAP SUNGAI APIT - Setiawan, Arif; Zainur, zainur; Nita Wijayanti, Ni Putu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The problem of the research is ability of Drilling in Soccer team of SSB SAP Sungai Apit still far from expectation, So when the player transfer the ball, they can across the enemies easily then win the match. it can be seen from try out and friendly match even more a big match and this is one of the factor why they loss. This research was done at Soccer team of SSB SAP Sungai Apit. This research used Experiment design to see the effect of using “Drill 11 The purpose of the research was to see the effect of using Drill 11 toward the ability of Drilling in Soccer team at SSB SAP Sungai Apit. The population of this research was soccer team player SSB SAP Sungai Apit district totaling 16 people. Exercise in this study is drill 11. The sampling technique used the total sampling, which was all the population had become the sample. The technique of collecting data was gotten from pre-test and post-test. The instrument of the research was a Dribbling test. The data analyzed by using T-test. Based on the data analysis, it can be seen from Tcount was 4,0 and Ttable 1,753. it meant Tcount>Ttable with the significant a=0,05. In conclusion, there was a different significant from Drill 11 in Soccer team of SSB SAP Sungai Apit.Keywords: Drill 11, Dribbling, Soccer.